The Comparison of Metaphors Translation Strategies in Subtitling of the King’s Speech Film - Gerson Sitanggang; Gunawan Tambunsaribu (Prodi Sastra Inggris UKI, 2023)
This research aims to compare the use of translation strategies used between humans and YouTube’s automated machine translator. This study employed the descriptive qualitative method. The writers collected data using a note-taking strategy. Based on the research findings, there are sixteen data that use metaphors. Six data use “anthropomorphic metaphor”; five data use “dead metaphor”; four data use “concrete to abstract metaphors”; and one datum uses “live metaphor”. This research shows that only three out of seven metaphor translation strategies are employed by human translators and YouTube. They use translation strategies “reproducing the same image in the TL”, “replacing the image in the SL with a standard TL image”, and “deletion”. The human translator uses “reproducing the same image in the TL” ten times, “replacing the image in the SL with a standard TL image” five times, and “deletion” once. YouTube uses “reproducing the same image in the TL” thirteen times and “replacing the image in the SL with a standard TL image” three times. Keywords: translation, metaphor, translation strategy, subtitle.